1991
DOI: 10.1038/clpt.1991.63
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of didanosine in patients with acquired immunodeficiency syndrome or acquired immunodeficiency syndrome—related complex

Abstract: The pharmacokinetics of didanosine (2',3'-dideoxyinosine) after intravenous and oral administration were evaluated in an open, escalating-dose phase I study in patients with acquired immunodeficiency syndrome (AIDS) or severe AIDS-related complex. Didanosine was administered twice a day for 2 weeks as an intravenous infusion of 60 minutes duration at doses ranging from 0.4 to 16.5 mg/kg, followed by 4 weeks of oral treatment at twice the intravenous dose. Serial blood and urine samples were obtained on the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 0 publications
6
47
0
Order By: Relevance
“…Of the quantity that reaches systemic circulation, 30 to 50% appears in urine as an unchanged drug; the remainder is excreted as various metabolites, which appear to be products of xanthine oxidase or other purine metabolic pathways (11,14). In dogs that receive ddI under conditions that mimic those in humans, the bioavailability and t 1/2 of ddI are similar to (10a).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Of the quantity that reaches systemic circulation, 30 to 50% appears in urine as an unchanged drug; the remainder is excreted as various metabolites, which appear to be products of xanthine oxidase or other purine metabolic pathways (11,14). In dogs that receive ddI under conditions that mimic those in humans, the bioavailability and t 1/2 of ddI are similar to (10a).…”
Section: Discussionmentioning
confidence: 61%
“…The commercial formulations of ddI (tablets and buffered powder) differ in bioavailability (3a, 14, 20), and all dosage forms include buffers to increase stability in gastric fluids. Systemic availability appears to be further compromised by a rate-limited absorption step (8,12,14), leading to recommendations that ddI be taken BID instead of once a day (3a, 8). With the ddI formulations used in this trial (taken BID under fasting conditions), mean systemic bioavailability has been reported to range from 33 to 41% (8,14,15,18,22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 8 and 10 a.m. the rats received a dose of ddI and/or AZT by intravenous injection. In patients, the concentrations in plasma are less than 10 to 20 ,ug/ml for AZT (9) and ddl (10). In this study, we used a dose of 40 mg/kg to give maximal concentrations in plasma of approximately 100 ,ug/ml for both drugs, because pharmacokinetic interactions such as inhibition of drug metabolism are expected to be more pronounced in the presence of higher concentrations in plasma.…”
mentioning
confidence: 99%